2013
DOI: 10.7860/jcdr/2012/4858.2684
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP in Myocarditis after a Scorpion Sting Envenomation

Abstract: Objective: This study was to evaluate the levels of NT-proBNP in patients with myocarditis which occurred after a scorpion sting envenomation. Material and Methods:A total of 30 patients with scorpion sting envenomation and 21 patients with heart failure which was caused by cardiomyopathy, were prospectively studied. The data included the patient demographics, clinical features, echocardiography and the NT-proBNP levels.Results: An echocardiographic evidence of myocarditis with a left ventricular ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…Similar finding has been reported by our group [22]. In a recently reported study, newer biomarker like N terminal pro BNP estimation could predict presence of myocardial dysfunction [23].…”
Section: Internal Medicine Sectionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar finding has been reported by our group [22]. In a recently reported study, newer biomarker like N terminal pro BNP estimation could predict presence of myocardial dysfunction [23].…”
Section: Internal Medicine Sectionsupporting
confidence: 78%
“…Bosnak et al, noted that no clinically useful demographic or epidemiological data to guide decision making regarding the need for intensive care unit admission in paediatric victims [19]. Biomarkers like cTnI may be useful adjunct to clinical and echocardiographic findings [19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…The cardiac involvement observed manifests clinically mainly as a reversible acute left ventricle (LV) dysfunction of different degrees of severity, with altered global or regional mobility occurring soon after the sting, and possible progression to APE. It is accompanied by increased serum levels of cardiac markers, as well as by changes in the electrocardiogram (ECG) and echocardiogram (ECHO) readouts (3) (33) (34) (35) (36) (37) (38) (39) (40) (41) . Another characteristic of the cardiac dysfunction mediated by catecholamine concerns the ECHO, whose fi ndings do not follow the anatomic distribution of the coronary arteries.…”
Section: Complications Of Scorpion Envenomingmentioning
confidence: 99%
“…Studies concerning envenomation have found that creatinine phosphatase, troponin, and NTproBNP increase after scorpion stings. 4,24,28,29 Examination of the literature concerning biochemical markers studied in scorpion envenomations indicates that troponin I levels have high sensitivity and specificity in determining scorpion stingÀrelated cardiac response. 4,30 Cupo et al 31 reported that troponin I values did not increase at first presentation in patients with cardiac dysfunction but rose subsequently, reaching maximum levels 24 to 36 h after scorpion sting.…”
Section: Discussionmentioning
confidence: 99%